Zarządzanie zbiorami nowoczesnej biblioteki naukowej - równowaga tradycji i nowoczesnych trendów - Poślada, Urszula (Archiwa, Biblioteki i Muzea Kościelne, 2016)
The effective management of the collections of a modern academic library, a research library involves managing the full library collection: both printed and electronic one; maintaining the proper balance between the accumulation of the relatively permanent printed collections and variable, dynamic electronic ones; it also means making collections accessible in the way that satisfies the user and promoting them relentlessly.